Mapping Global Trends in Fruit and Vegetable Waste Research: A Bibliometric and Keyword Analysis - Adelia Suryani; Muhammad Fadli Ramadhansyah (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Fruit and vegetable waste significantly contributes to nutrient loss, food insecurity, and the transmission of waste-related diseases, particularly in low- and middle-income countries. Understanding how global research has evolved on this topic is essential to guide effective interventions, enhance cross-country collaboration, and prioritize research efforts in regions facing the most severe waste-related challenges. This study aims to analyze the global development of research on fruit and vegetable waste to identify patterns, gaps, and opportunities for addressing critical challenges such as environmental degradation, inefficiencies in food systems, and public health implications. A bibliometric analysis was conducted using the Scopus database, focusing on English-language, open-access journal articles published between 1965 and 2024. Keyword searches were validated through manual screening to ensure relevance and duplicate or unrelated records were excluded. The final dataset consisted of 1,192 publications. VOSviewer software was employed to performed co-authorship, co-occurrence, citation, and clustering analyses. The results indicate amarked increase in research activity from 2019 to 2024, with the United States (186 articles), Spain (107 articles), and Italy (102 articles) emerging as leading contributors. The most dominant keyword was “food waste” with recent research trends focusing on sustainability, valorization, circular economy, and links to nutrition and food security. These findings offer actionable insights for policymakers, researchers, and practitioners in developing integrated strategies that address both environmental and public health dimensions of fruit and vegetable waste.